Assessment of Immunoglobulins In The Serum Of Children With Shigellosis - Falih , Talib (University of Thi-Qar Journal of Science, 2019)
During a period of nine months from January 2006 to September 2006. Sixty –two cases of shigellosis were collected at Nassiria Pediatric hospital ( Age ranged from one day to five years). A total of 317 cases suffering form bloody diarrhea , out of 317 stool samples , 62 bacterial isolates were obtained represent 19.5% from all cases of diarrhea ,The isolates identified were, Shigella dysenteriae , Shigella sonnei , Shigella boydii , and Shigella flexneri .The percentage of each are , 22(35.4%) , 19(30.6%) , 13(20.9%) , 8(12.9%) respectively . Shigellosis was predominant in those below one year of age (32.2%) .The concentration of total protein level in the serum of children with shigellosis was normal in all age groups , while albumin was low , alpha 1 – globulin concentration was high , alpha 2 –globulin increased slightly with advancing age , beta – globulin concentration in serum of children was normal , gamma globulin concentration was slightly elevated in most age groups . Forty – seven children (75.8%) are found to have high level of lmmunoglobulins concentration while fifteen children ( 24.2%) have low levels of lmmunoglobulin concentration .They are classified as follows : 11.2% have IgA deficiency , 5.1% have IgM deficiency and 4.8% have IgG deficiency.These results revealed that Ig deficiency is associated with shigellosis .